Cold plasma assisted deposition of organosilicon coatings on stainless steel for prevention of adhesion of Salmonella enterica serovar Enteritidis. Issue 2 (21st February 2021) - Hage, Mayssane; Khelissa, Simon; Abdallah, Marwan; Akoum, Hikmat; Chihib, Nour-Eddine; Jama, Charafeddine
Abstract: The persistence of Salmonella enterica on abiotic surfaces in hospitals and the agri-food industries leads to several infections worldwide. In this context, this work aimed to study the adhesion of S. Enteritidis on plasma-modified stainless steel to prevent biofilm-associated-infections. Surface modification was achieved by the elaboration of organosilicon coatings from the monomer 1, 1, 3, 3-tetramethyldisiloxane, mixed with oxygen, using a flowing nitrogen microwave post-discharge plasma polymerization technique. The effect of cold plasma parameters on the properties of the coatings, the coated surface topography and S. Enteritidis cell adhesion was studied. The results showed that the surface topography influenced the bacterial adhesion rate. Indeed, rough surfaces did not repel S. Enteritidis since the number of attached cells on these coatings was between 30 ± 4 to 65 ± 4 bacteria per microscopic field. Otherwise, smoother surfaces demonstrated an anti-adhesive character since the number of attached cells was almost nil on these coatings. Graphical Abstract: